Assessing effects of the entomopathogenic fungus Metarhizium brunneum on soil microbial communities in Agriotes spp. biological pest control. Issue 10 (11th September 2017) - Mayerhofer, Johanna; Eckard, Sonja; Hartmann, Martin; Grabenweger, Giselher; Widmer, Franco; Leuchtmann, Adrian; Enkerli, Jürg
Abstract: The release of large quantities of microorganisms to soil for purposes such as pest control or plant growth promotion may affect the indigenous soil microbial communities. In our study, we investigated potential effects of Metarhizium brunneum ART2825 on soil fungi and prokaryota in bulk soil using high-throughput sequencing of ribosomal markers. Different formulations of this strain, and combinations of the fungus with garlic as efficacy-enhancing agent, were tested over 4 months in a pot and a field experiment carried out for biological control of Agriotes spp. in potatoes. A biocontrol effect was observed only in the pot experiment, i.e. the application of FCBK resulted in 77% efficacy. Colony counts combined with genotyping and marker sequence abundance confirmed the successful establishment of the applied strain. Only the formulated applied strain caused small shifts in fungal communities in the pot experiment. Treatment effects were in the same range as the effects caused by barley kernels, the carrier of the FCBK formulation and temporal effects. Garlic treatments and time affected prokaryotic communities. In the field experiment, only spatial differences affected fungal and prokaryotic communities. Our findings suggest that M. brunneum may not adversely affect soil microbial communities. Abstract : Formulated Metarhizium brunneum has small and temporal effects on fungal communities in a pot experiment and no effects were detected in the field.